The Psychodynamics of Manar in the Novel Shurfat al-‘Aar by Ibrahim Nasrallah - Hikmah, Nadiatul; Syah, Ahfa Rahman (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2024)
Shurfat al-‘Ār by Ibrahim Nasrallah delves into the psychological dynamics of the character Manar. In the novel, the main character, Manar, becomes a victim of rape committed by Yunus, the antagonist. This event leads to serious psychological consequences for Manar. This study explores the psychodynamics of Manar, including the dynamics of her id, ego, and superego, as well as her anxiety and defense mechanisms. The research uses a descriptive qualitative method, which includes describing the facts followed by an analysis of the text using Sigmund Freud’s psychoanalytic theory. The results show that the dynamics of the id, ego, and superego play a significant role in how Manar copes with her traumatic experience. The character of Manar also experiences the three types of anxiety conceptualized by Freud: objective anxiety, neurotic anxiety, and moral anxiety. The form of fear from a real threat is a result of objective anxiety, the inner pressure she feels represents neurotic anxiety, and the fear of committing wrongdoing related to morals, customs, and norms is a form of moral anxiety. The defense mechanisms that develop within Manar are her efforts to cope with the pressure and anxiety, including repression, regression, denial, sublimation, isolation, rationalization, and dissocia